International economic instability : the experience after world war II - Coppock, Joseph David (New York : McGraw-Hill, 1962)
The subject covers a wide range of International/foreign trade; its strengths and weaknesses.
Includes bibliographical references and index.
ne 20/02/2018
Loans
Keywords: International Economic Relations; Commerce